2022
DOI: 10.1039/d2cc03619c
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic catalysis of graphitic carbon nitride supported bimetallic sulfide nanostructures for efficient oxygen generation

Abstract: Herein, a series of g-C3N4 supported bimetallic sulfide nanostructures (Ni3S2/MoS2/ng-C3N4, n = 10, 20 and 30) was prepared by a hydrothermal method and subsequently a thermal annealing approach. Ni3S2/MoS2/20g-C3N4 with...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…It is shown that the reaction of S element with Ni produces S metallized metal. 16 In Fig. S3d and e, † the Fe 2p and Mo 3d spectra further confirm the nanosheets are FeMoO 4 .…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…It is shown that the reaction of S element with Ni produces S metallized metal. 16 In Fig. S3d and e, † the Fe 2p and Mo 3d spectra further confirm the nanosheets are FeMoO 4 .…”
mentioning
confidence: 56%
“…It is shown that the reaction of S element with Ni produces S metallized metal. 16 In Fig. S3d and e To explore the evolutionary process detail of morphology, the XRD patterns and SEM images of Ni 3 S 2 -FeMoO 4 with different hydrothermal treatment times were displayed in Fig.…”
mentioning
confidence: 99%
“…A similar result was also reported in previous literature. 18 A uniform distribution of Mo and O as well as N and Fe is observed in the elemental mapping images of Fe-Mo 5 N 6 /MoO 3 -550 (Fig. 3b-e), further revealing the coexistence of MoO 3 , M 5 N 6 and Fe ions in the desired hybrid catalyst.…”
Section: Dalton Transactions Papermentioning
confidence: 78%
“…Notably, the OER performance of Fe-Mo 5 N 6 /MoO 3 -550 is one of the best activities previously reported from non-noble OER systems (Table S1†). It is clear that the catalytic activity of Fe-Mo 5 N 6 /MoO 3 -550 is better than or comparable to those of P-MoO 3 FCL MXene/NF, 17 g-C 3 N 4 supported bimetallic sulfide nanostructures, 18 Mo-doped CoP 2 hybrid electrocatalysts, 20 porphyrin coordination polymer/Co 1− x S composite electrocatalyst, 21 NiO@MoO 3 /VC, 22 Mo-doped Ni 3 Fe/Ni 3 FeN, 23 ZIF67@MoO 3 NSs@NF, 24 CoSe@NiSe 2 @MoS 2 heterostructured composites, 25 and so on. The excellent OER performance of Fe-Mo 5 N 6 /MoO 3 -550 might correlate with its enriched active sites.…”
Section: Resultsmentioning
confidence: 99%
“…5 Although scarce and expensive Ir- and Ru-based oxides can be used to reduce the energy barriers for the OER, their wide applications are limited. 6–8 Therefore, developing efficient and earth-abundant transition-metal-based electrocatalysts, such as metal sulfides, 9,10 phosphides, 11 oxides, 12,13 etc. , to enhance the OER performance is urgently needed.…”
mentioning
confidence: 99%